Unraveling the mechanisms of reputation and alliance formation: A study of venture capital syndication in China - Gu, Qian; Lu, Xiaohui (Strategic Management Journal, 2014)
Extant research shows that resources are significant to a firm's choice of alliance formation. We focus on an important form of intangible resource—firm reputation—and examine how it affects a firm's propensity to form alliances. We propose an inverted U‐shaped relationship between a firm's reputation and its likelihood of alliance formation, resulting from the opposing mechanisms of opportunity and need. We also examine how this relationship may vary across two contingencies: (1) foreign and domestic firms; and (2) different levels of institutional development. Empirical analyses of China's venture capital ( VC ) industry provide support for our hypotheses . Copyright © 2013 John Wiley & Sons, Ltd.